2003
DOI: 10.1042/cs20020360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of menstrual cycle phase on the concentration of bioavailable 17-β oestradiol and testosterone and muscle strength

Abstract: To investigate the effect of changes in sex hormone concentration on muscle strength and the bioavailability of 17-beta oestradiol (oestradiol) and testosterone, seven eumenorrheic females were tested during two phases of the menstrual cycle. Maximum voluntary isometric strength of the first dorsal interosseus muscle was measured during the early follicular and mid-luteal phases of the menstrual cycle. These phases were chosen for testing as the concentration of total oestradiol is significantly different in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 33 publications
3
74
0
Order By: Relevance
“…Thus, the variations in the hormonal concentrations would provide better performance in the follicular phase. Nevertheless, the evidence does not support this statement (4,(8)(9)(10)17,19) . Reviewing the literature, it is observed that the issue of strength performance concerning the different phases of the MC still remains controverse (2,5,7) .…”
Section: Lutealmentioning
confidence: 44%
See 3 more Smart Citations
“…Thus, the variations in the hormonal concentrations would provide better performance in the follicular phase. Nevertheless, the evidence does not support this statement (4,(8)(9)(10)17,19) . Reviewing the literature, it is observed that the issue of strength performance concerning the different phases of the MC still remains controverse (2,5,7) .…”
Section: Lutealmentioning
confidence: 44%
“…However, the literature presents controversial results (5,7) . While some evidence demonstrates there are not significant differences in physiological aspects (O 2 consumption, lactate threshold, plasmatic volume, hemoglobin concentration and ventilation) in the three phases of the MC (2) , other studies (4,(8)(9)(10) have verified differences in the hormonal concentrations, with no alteration in muscle strength between phases. Dias et al (11) assessed strength in two multiarticular resisted exercises for large muscular groups and did not find significant differences between the different phases of the MC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45][46][47][48][49] If additional future data do develop to show a trend like that, then this may be seen as a limitation.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%